Assessment of oral stereognostic ability and cognitive status in dental implant patients compared to partially edentulous and fully dentate individuals - Ali, Rihab A; Diab, Ban S; Ali, Lashin S (Journal of Baghdad College of Dentistry, 2025)
Background: The oral stereognostic ability (OSA) examines an individual’s oral functioning and determines how patients respond to various dental therapy. Natural tooth loss may result in a reduction in oral perception. Reduced oral perception has been linked to cognitive deterioration in the elderly. The aim of this study was to assess the oral stereognostic ability among dental implant patients in relation to cognition status and compare them with partially edentulous and fully dentate patients. Material and method: The study group included 90 dental implant patients aged 50-60 years old compared with partially edentulous and fully dentate patients. Five different test samples were used to assess the oral stereognostic ability including (cubic, circle, pyramid, star and cross). The criteria for the assessment of oral stereognostic ability were the time required for the patient to recognize the shape of the samples. The cognition status was assessed using the Self-Administered Gero-cognitive Examination (SAGE) test according to which the participants were divided into two groups poor and good. Data were statistically analyzed using SPSS 22, Chicago, Illinois, USA. Results: The mean time is taken to recognize the shape of all samples was less in the fully dentate group followed by the implant group and then the partially edentulous group with a statistically significant difference. Concerning the cognition status, the mean time taken to distinguish the shape of all sample were significantly higher among person with poor than good cognitive status for implant, partially edentulous and fully dentate groups. Conclusion: The results of the current research revealed that loss of natural teeth decreases both cognitive status and oral perception represented by oral stereognosis ability as the oral stereognosis of partially edentulous subjects was significantly poorer than that of fully dentate subjects.